Underestimation of mycobacterium tuberculosis infection in HIV-infected subjects using reactivity to tuberculin and anergy panel - García García, Maria de Lourdes (2000)
Background. This study aimed to evaluate purified protein derivative (PPD) reactivity and its interrelationship with anergy panel and CD4+ lymphocytes in HIV-infected subjects as compared to PPD reactivity in HIV-uninfected individuals in a tuberculosis endemic and high Bacillus Calmette-Guerin (BCG) coverage environment. Methods. Clients of four Mexico City HIV detection centres were screened for HIV-1 anti-bodies (ELISA or haemagglutination, Western Blot); reactivity to PPD (Mantoux PPD, 5TU RT-23), Candida (1:1000, 0.1 ml), and tetanus toxoid (10Lf, 0.1 ml); and CD4+ T cells. Active tuberculosis was excluded. Informed consent was obtained. Results. From 5130 clients 1168 subjects were enrolled; of these 801 (68.6%) were HIV positive. Reactivity to PPD among HIV-positive subjects was found in 174 (22%), 261 (32.6%), and 296 (37%), at PPD cutoff levels of ≥10 mm, ≥5 mm, and ≥2 mm as compared to 224 (61%) of 367 HIV-negative individuals' reactors to PPD (≥10 mm) (P<0.001). After exclusion of anergic individuals using two cutoff levels for cutaneous allergens (≤2 mm and ≤5 mm), PPD reactivity between HIV-infected and uninfected individuals continued to be significantly different. Only HIV-infected individuals with CD4+ T cells ≥500 cells/mm3 had similar reactivity to PPD as HIV-uninfected individuals. Variables associated with PPD reactivity were CD4+ T cell counts, BCG scar, HIV infection and age. Conclusions. PPD reactivity was useful to diagnose tuberculosis infection only among HIV-infected individuals with CD4+ counts ≥500 cells/mm3. Among individuals with lower counts, lowering cutoff levels or using anergy panel did not permit comparable reactivity as that observed among HIV-uninfected individuals.